Phytochemicals from Calophyllum depressinervosum - Nor Hisam, Zamakshshari; Ee, G.C.L.; Daud, S.; Teh, S.S.; Mah, S.H. (ASIAN PUBLICATION CORPORATION, 2018)
A phytochemical investigation on the stem bark of Calophyllum depressinervosum resulted in the isolation of four xanthones, one coumarin and one kavalactone which were elucidated to be caloxanthone B (1), caloxanthone I (2), caloxanthone J (3), xanthochymone B (4), calopolynolide B (5) and desmethoxyyangonim (6). The structures of the compounds were elucidated using spectroscopic analysis such as 1D and 2D NMR together with MS technique. The dichloromethane extract of Calophyllum depressinervosum gave good cell viability on RAW246.7 cells for potential antiinflammatory test with an IC50 value of 17.19 ± 0.007 µg/mL.